Can lubricant enhance the torque of ultrasonic motors? An experimental investigation - Qiu, Wei ; 0000-0003-3032-4172; Mizuno, Yosuke; Tabaru, Marie; Nakamura, Kentaro (Applied Physics Letters, 2014)
Lubrication has been proven to be an effective approach to drastically improve the efficiency of ultrasonic motors without losing the output torque. This phenomenon is attributed to the effective modulation of the friction force by lubricant, according to the theory described in the Stribeck curve. Previous findings even show a potential to increase the motor output torque with lubrication. Here, the torque enhancement of ultrasonic motors using lubricant is extensively studied in hybrid transducer-type ultrasonic motors (HTUSMs) with a size of 25 mm in diameter. The lubricated HTUSMs could withstand static preload as high as 267 N and maximum torque as large as 1.01 N m was obtained with lubrication, which were 3.5 times and 2.6 times higher than those in dry condition, respectively. This result clearly reveals that lubrication can enable ultrasonic motors to be operated under much higher static preload and hence significantly improve the motor output torque, instead of only reducing the friction force.